Opportunities for Social Engagement of Business Student Leaders - Legaspi, Erika Joy M. (ASEAN Journal of Education, 2017)
Membership in affiliate professional organizations is a form of social engagement that has proven beneficial to students. It has an important role in their leadership and career preparation. This study was conducted to identify the opportunities for social engagement of business student leaders, specifically the accountancy students who run as officers for the Junior Philippine Institute for Accountants (JPIA). The main instrument used in this study was a survey questionnaire that was administered to 62 officers of JPIA from Region IV-A. The study found out that there were a lot of opportunities for social engagement that were made available to the JPIA officers, such as leadership seminars, regional and national seminars, conferences and conventions related to accounting, firm visits, planning sessions with accounting professionals, general assemblies, academic and non-academic competitions, and outreach activities. They were also introduced to the environment and activities of the accounting profession. The officers likewise developed the values of fellowship and solidarity with the other chapters, social awareness through the different outreach activities, as well as the moral values central to the accounting profession. It is recommended that, since membership in student or junior affiliates of a professional organization has proven beneficial to the student-members, there should be concerted efforts on the part of the faculty and school administrators to encourage their students to join these organizations.